Development of Teaching Factory Learning Guidebooks Through Subject Integration in Vocational Schools - Cholis, Nur; Zuriah, Nurul; Poerwanti, Endang (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Project-based TEFA at SMK Muhammadiyah 1 Kepanjen was running and industry-synchronous, yet cross-subject integration (general ↔ vocational) had not been implemented and evaluation documents were inconsistent (~10% incomplete). This development study produced a Teaching Factory (TEFA) learning guidebook that integrates general and vocational subjects in the Motorcycle Engineering concentration using ADDIE (analysis, design, development, implementation, evaluation). Participants in a limited implementation comprised 4 expertise teachers, 3 general-subject teachers, 4 vocational-subject teachers, 10 Grade-XI students, 2 industry representatives, the principal, and the vice principal for curriculum (N=25). Instruments included design/material expert checklists and stakeholder feasibility/usability questionnaires (Likert 1–5) plus observation, interview, and documentation guides. Scale anchors, item counts, and example items are specified in Methods; internal consistency (Cronbach’s α/ω) and inter-rater agreement for expert validations are reported in Results. Feasibility was high (expert means ≈4.6/5) and stakeholder ratings averaged 88–94% across ease of use, relevance, completeness/integration, clarity, and practical applicability. Key improvements include integrated performance assessment (multi-rater, role-inclusive), richer cross-subject cases, and documentation consistency. Findings are feasibility-oriented and do not claim effectiveness; future work should test outcomes and employability impacts via quasi-experimental designs.